Gag-Gag Interactions Are Insufficient to Fully Stabilize and Order the Immature HIV Gag Lattice - Ipsita Saha; Benjamin Preece; Abby Peterson; Haley Durden; Brian MacArthur; Jake Lowe; David Belnap; Michael Vershinin; Saveez Saffarian (Viruses, 2021)
Immature HIV virions harbor a lattice of Gag molecules with significant ordering in CA-NTD, CA-CTD and SP1 regions. This ordering plays a major role during HIV maturation. To test the condition in which the Gag lattice forms in vivo, we assembled virus like particles (VLPs) by expressing only HIV Gag in mammalian cells. Here we show that these VLPs incorporate a similar number of Gag molecules compared to immature HIV virions. However, within these VLPs, Gag molecules diffuse with a pseudo-diffusion rate of 10 nm2/s, this pseudo-diffusion is abrogated in the presence of melittin and is sensitive to mutations within the SP1 region. Using cryotomography, we show that unlike immature HIV virions, in the Gag lattice of VLPs the CA-CTD and SP1 regions are significantly less ordered. Our observations suggest that within immature HIV virions, other viral factors in addition to Gag, contribute to ordering in the CA-CTD and SP1 regions.